Up scaling table grape water requirements in the Low-Middle São Francisco river basin, Brazil - De, A. H.; Lopes, H. L.; Hernandez, F. B.T. [UNESP] (International Society for Horticultural Science (ISHS), 2014)
Landsat satellite images and a net of 15 agro-meteorological stations were used together for determining actual evapotranspiration (ET) and crop coefficient (Kc) of table grapes on a large scale in the Low-Middle São Francisco river basin. Inside the area covered by the stations, a commercial table grape farm, with a mixture of varieties located in the Petrolina-PE municipality, Brazil, was used for modelling vineyard water variables. The application of a relation between Kc and the accumulated degree days (DDac), together with weather data for 2011, allowed the quantification of vineyard water requirements (VWR) along the crop stages and for a whole generalized growing season (GS) in the centre of development of Petrolina/Juazeiro, considering three pruning dates covering different weather conditions and an average four months GS. Comparing the results for the pruning periods studied, the highest water requirements were when the pruning is done from September to December, with an averaged VW RGS value of 620 mm. On the other hand, the lowest rates are for pruning dates in May, when the VWRGS values were around 460 mm. Due to a higher atmospheric demand in Petrolina, Pernambuco (PE) state compared to Juazeiro, Bahia (BA) state, the first presented a mean VWRGS about 8% higher than that found for Juazeiro. The results of the current research are important to subsidize the table grapes water management and to ensure their water availability in the actual conditions of land and climate changes in the Brazilian semi-arid region.
Keywords: Actual evapotranspiration; Crop coefficient; Degree-days; Remote sensing; Vineyards